Hubungan Program Kesehatan dan Keselamatan Kerja (K3) dengan Produktivitas Kerja - Ikhtiar, Muhammad; Imaduddin , Muh Fauzan; Fachrin , Suharni A. (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2024)
Work productivity in a company has an important role. The success or failure of a company really depends on the ups and downs of employee work productivity in a company. Several factors that can influence work productivity include motivation, work ethic, commitment and satisfaction. This research aims to determine the relationship between occupational health and safety programs and work productivity at PT PLN UP2B Makassar City System in 2023. The type of research used is quantitative research with a cross sectional approach. The population in this study was 87 respondents. The sampling technique is total sampling. The sample was 87 respondents. The instrument used in this research was a questionnaire. The results of the research show that there is a relationship between motivation and work productivity at PT PLN UP2B Makassar City System in 2023 (p = 0.004 < 0.05), there is a relationship between commitment and work productivity at PT PLN UP2B Makassar City System in 2023 (p = 0.028 < 0.05), there is a relationship between work ethic and work productivity at PT PLN UP2B Makassar City System in 2023 (p = 0.000 < 0.05), there is a relationship between attendance and work productivity at PT PLN UP2B Makassar City System in 2023 ( p = 0.044 < 0.05). The conclusion of the research is that all variables in this research including motivation, commitment, work ethic and compliance have a relationship with work productivity at PT PLN UP2B Makassar City in 2023. This research suggests that the company provides information related to the implementation of K3 on a regular basis as a form of improvement effort. Awareness in carrying out actions related to K3 policies during work. Keywords : Motivation, Work Ethic, Commitment, Work Productivity